Development of Traditional Herbal Medicine through Product Innovation and Marketing Innovation using Business Model Canvas Analysis - Karlina; D A Wahab Sya’roni (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The Covid-19 pandemic has had a major impact on the world economy, including Indonesia. Large, medium and small scale companies must make various adjustments including product innovation and marketing strategy innovation to face the current economic conditions. One of the small industries affected is herbal medicine business. The purpose of this research is to develop a traditional herbal medicine business through product innovation and digital marketing strategy innovation to increase consumer buying interest and product selling value using business model canvas analysis and SWOT analysis. This study used descriptive qualitative method and literature study. Data collection techniques using in-depth interviews, observations, and questionnaires for herbal medicine makers, sellers, and consumers. The results show that product innovation and marketing innovation can increase consumer buying interest and increase the selling value of the product. The conclusion of this study, herbal medicine is a traditional drink that can compete and survive the economic crisis through product innovation and marketing innovation that continues to be developed